The Voice of the Subaltern's Subaltern The Tionghua Peranakan Women Writers (1908-1935) - Cheang, Sim Chee (Jurnal Peradaban Melayu, 2003)
In her article "Can the Subaltern Speak?" (Spivak 1996), Gayatri Spivak argues that the subaltern's voice cannot be heard and will not be heard because of the all consuming power of a hegemony and the "nostalgia for lost origins" (1996: 204) which necessarily envelopes the subaltern. Ironically, her doubts in retrieving subaltern history follows her initial calls for Subaltern Studies to include the female subaltern.